Menanamkan Nilai Karakter Bergotong Royong Melalui Ekstrakulikuler Seni Tari Bertema Sikap Peduli Lingkungan di SDN 77 Kota Bengkulu - Puja Rapita; Abdul Muktadir; Bambang Parmadi (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to describeinstilling the character value of working together through dance extracurricular activities with the theme of caring for the environment at Elementary School 77, Bengkulu City.  This type of research is qualitative research with the research subjects being students in grades IV and V who took part in dance extracurricular activities at SDN 77 Bengkulu City. Technique Data collection in this research was carried out by interviews, observations, and documentation during the process of extracurricular dance activities. Instruments used in this research, namely interview guidelines and observation guidelines. Data analysis technique using the Spradley model, namely taxonomic analysis. Test the validity of the data via increased persistence,triangulation, and membercheck. The results of this research show that through extracurricular activities the art of dance can instill the value of cooperative character cooperation with students which can be seen through the mutual cooperation aspect 1) Aspect Respecting other people, including using polite language towards friends, dance instructors, and also researchers. 2) The mutual help aspect, which includes helping each other teach movements throwing rubbish carelessly, movements imitating floods, sweeping movements, planting. 3) Aspect deliberation to reach consensus, which includes determining the dance movements that will be performed worn, determining dance patterns, and determining costumes when performing. Conclusions of This research, namely dance extracurricular activities, can instill the value of cooperative character collaborate with students by producing a dance with the theme of caring environment.